FASCIN regulates actin assembly for spindle movement and polar body extrusion in mouse oocyte meiosis. Issue 11 (21st May 2021) - Hu, Lin‐Lin; Pan, Meng‐Hao; Yang, Feng‐Lian; Zong, Zi‐Ao; Tang, Feng; Pan, Zhen‐Nan; Lu, Xiang; Ren, Yan‐Ping; Wang, Jun‐Li; Sun, Shao‐Chen
Abstract: During mouse oocyte meiotic maturation, actin filaments play multiple roles in meiosis such as spindle migration and cytokinesis. FASCIN is shown to be an actin‐binding and bundling protein, making actin filaments tightly packed and parallel‐aligned, and FASCIN is involved in several cellular processes like adhesion and migration. FASCIN is also a potential prognostic biomarker and therapeutic target for the treatment of metastatic disease. However, little is known about the functions of FASCIN in oocyte meiosis. In the present study, we knocked down the expression of FASCIN, and our results showed that FASCIN was essential for oocyte maturation. FASCIN was all expressed in the different stages of oocyte meiosis, and it mainly localized at the cortex of oocytes from the GV stage to the MII stage and showed a similar localization pattern with actin and DAAM1. Depletion of FASCIN affected the extrusion of the first polar body, and we also observed that some oocytes extruded from the large polar bodies. This might have resulted from the defects of actin assembly, which further affected the meiotic spindle positioning. In addition, we showed that inhibition of PKC activity decreased FASCIN expression, indicating that FASCIN might be regulated by PKC. Taken together, our results provided evidence for the important role of FASCIN on actin filaments for spindle migration and polar body extrusion in mouse oocyte meiosis. Abstract : Our results provided evidence for the important roles of FASCIN on actin filaments for spindle migration and polar body extrusion in mouse oocyte meiosis.